United Kingdom : Financial Sector Assessment Program-Financial System Stability Assessment. (IMF Staff Country Reports; Country Report ;, 2016)
This paper assesses the stability of the financial system of the United Kingdom as a whole, not that of individual institutions. Since the last Financial Sector Assessment Program (FSAP), the U.K. financial system has put the legacy of the crisis behind it and has become stronger and more resilient. This FSAP found the system to be much stronger and thus better able to serve the real economy. Like all systems, the U.K. financial system is exposed to risks. Its position as a global hub exposes the U.K. financial system to global risks. In addition, the uncertainties associated with the possibility of British exit from the EU weigh heavily on the outlook.